Filling in missing sea-surface temperature satellite data over the Eastern Mediterranean Sea using the DINEOF algorithm - Nikolaidis, Andreas; Georgiou, Georgios C.; Hadjimitsis, Diofantos G.; Akylas, Evangelos (My University, 2014)
The Data Interpolating Empirical Orthogonal Functions method is a special technique based on Empirical Orthogonal Functions and developed to reconstruct missing data from satellite images, which is especially useful for filling in missing data from geophysical fields. Successful experiments in the Western Mediterranean encouraged extension of the application eastwards using a similar experimental implementation. The present study summarizes the experimental work done, the implementation of the method and its ability to reconstruct the sea-surface temperature fields over the Eastern Mediterranean basin, and specifically in the Levantine Sea. L3 type Satellite Sea-surface Temperature data has been used and reprocessed in order to recover missing information from cloudy images. Data reconstruction with this method proved to be extremely effective, even when using a relatively small number of time steps, and markedly accelerated the procedure. A detailed comparison with the two oceanographic models proves the accuracy of the method and the validity of the reconstructed fields.
Keywords: Remote Sensing; Sea-surface temperature; DINEOF; Data reconstruction; Levantine Sea